Enhanced Photoreduction of U(VI) on C3N4 by Cr(VI) and Bisphenol A: ESR, XPS, and EXAFS Investigation - Wang, Huihui; Guo, Han; Zhang, Ning; Chen, Zhongshan; Hu, Baowei; Wang, Xiangke (Environmental science & technology, 2019)
The effect of Cr(VI) and bisphenol A (BPA) on U(VI) photoreduction by C3N4 photocatalyst was demonstrated by the batch experiments, electron spin resonance (ESR), X-ray photoelectron spectroscopy (XPS), X-ray absorption near edge structure (XANES), and extended X-ray absorption fine structure (EXAFS) techniques. The batch experiments manifested that Cr(VI) and BPA enhanced the photocatalytic activity of C3N4 for U(VI) photoreduction, whereas U(VI) photoreduction was significantly diminished with increased pH from 4.0 to 8.0. According to radical scavengers and ESR analysis, U(VI) was photoreduced to U(IV) by photogenerated electrons of conduction band edge, whereas Cr(VI) was reduced to Cr(III) by H2O2. BPA and its products such as organic acid and alcohols can capture photoinduced holes, which resulted in the enhancement of U(VI) photoreduction to U(IV). XPS and XANES analyses demonstrated that U(VI) was gradually photoreduced to U(IV) by C3N4 within irradiation 60 min, whereas U(IV) was reoxidized to U(VI) with increasing irradiation time. EXAFS analysis determined that the dominant interaction mechanisms of U(VI) on C3N4 after irradiation for 240 min were reductive precipitation and inner-sphere surface complexation. This work highlights the synergistic removal of radionuclides, heavy metals, and persistent organic pollutants by C3N4, which is crucial for the design and application of a high-performance photocatalyst in actual environmental cleanup.